The Gaps Between Current Management of Intracerebral Hemorrhage and Evidence-Based Practice Guidelines in Beijing, China - Li, Di; Sun, Haixin; Ru, Xiaojuan; Sun, Dongling; Guo, Xiuhua; Jiang, Bin; Luo, Yanxia; Tao, Lixin; Fu, Jie; Wang, Wenzhi (Frontiers in Neurology, 2018)
Background: Much less data on intracerebral haemorrhage (ICH) epidemiology are available from China. To date, current studies did not evaluate the consistency between clinical practice in the management of ICH and the recommendations in the evidence-based international practice guidelines. For exploring the agreement between the management strategies during the acute phase of ICH and Class I recommendations in current international practice guidelines in Beijing, China and elucidating the underlying reasons of any inconsistencies found, we retrospectively collected in-hospital data of ICH patients from 15 hospitals in Beijing during a 1-year period between January 2012 and December 2012. In addition, a total of 75 standardised questionnaires on the clinical management of ICH were distributed to 15 cooperative hospitals. Results: In this study, we included 1355 ICH patients. Various managements were highly consistent with Class I recommendations as follows: all of the patients underwent radiographic examination on admission; approximately 93% of survivors received health education and 84.5% of those diagnosed with hypertension were prescribed antihypertensive treatment at discharge; 91.8% of patients presenting with seizures received in-hospital antiepileptic drugs; 88% of patients with hyperglycaemia on admission were continuously monitored; Conversely, several aspects were extremely inconsistent with the guidelines as follows: only 14.2% of patients were initially managed in the neurological intensive care unit; 22.3% of bedridden patients received preventive treatment for deep vein thrombosis within 48 h of onset. The questionnaire results showed that imaging examination, blood glucose monitoring, and secondary prevention of ICH were found useful by more clinicians; that was not the case for neurological intensive care unit requirement. Regarding recognition to the guidelines, there were no significant differences among all subgroup (P>0.05). Conclusions: This is the first study to assess the consistency between clinical practice in the acute phase of ICH in China and current evidence-based guidelines. In addition, we elucidates some factors leading to inconsistencies between clinical practice in the acute phase of ICH and current evidence-based guidelines and therefore facilitate the development of management strategies to improve ICH care in in Beijing, China.